PENGARUH TINGKAT PENDIDIKAN DAN GENDER TERHADAP TINGKAT PENGANGGURAN TERBUKA DI JAWA TENGAH TAHUN 2019 - 2022 - Wahyulianti, Khofifah; Septiani, Eka Devi; Haryanti, Yuli; Setianingrum, Risma; Farliana, Nina (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Open unemployment is one of the main challenges in economic development, with the unemployment rate in Central Java fluctuating due to various factors, including education and gender. This study aims to analyze the influence of education level and gender on the Open Unemployment Rate (OUR) in Central Java Province during the period 2019–2022. The data for this study were obtained from the Central Bureau of Statistics (BPS) and analyzed using multiple linear regression with a quantitative approach. Our findings indicate that the level of education has a significant effect on the open unemployment rate. Meanwhile, the gender variable does not significantly affect the open unemployment rate. Simultaneously, education level and gender have a significant effect on the open unemployment rate, with a coefficient of determination (R²) of 41.5%, indicating that other factors beyond this study also influence the unemployment rate. Strategic measures are needed to reduce the Open Unemployment Rate (OUR) by strengthening the link between education and the industrial sector, as well as implementing responsive policies to support employment opportunities for all individuals.